Implementation of the program "development of potential of gifted teenagers in creative education" on the basis of educational institutions of the city of Orenburg - Ekaterina S. Mikhaleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the modern education system is increasing the demand for young people with a high level of development potential, therefore, the priority is the development of potential of gifted students, and a study of their problem areas and prospects of development is the most important task of modern education. Consequently, there is a need to create a new educational paradigm in modern education system with the priority of creative education, providing an opportunity for the development of potential of gifted adolescents, and orientation to the new tasks, finding a life perspective, the birth of many innovative ideas. An important role in the development of the potential of a gifted teenager in the creative education is given to the teacher. The article describes the insights on the opportunities for achieving productive development potential of a gifted teenager in creative education.